2012
DOI: 10.9734/ajea/2012/1211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NPK Fertilization on Cassava Mosaic Disease (CMD) Expression in a Sub-Saharan African Region

Abstract: The influence of NPK fertilizer on the incidence, severity and gravity of cassava mosaic disease (CMD) was investigated using eight genetically improved cassava varieties and eight local farmer's varieties. The study was carried out in a savannah region (Gandajika) in D.R. Congo at two locations. The varieties were planted with and without NPK fertilization. Application of NPK fertilizer significantly (P<0.05) increased CMD incidence, severity (AUDPC) and gravity overtime compared to the trials without fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
1
1
Order By: Relevance
“…It was shown that there was no significant effect of fertilizer on the disease severity of cassava plants. This is in disagreement with [33], who reported that NPK fertilizer application significantly increases CMD incidence and severity compared to trials without fertilizers. The disagreement observed in this investigation could have been as a result of high resistance of the improved cassava varieties used in this experiment to disease and pests.…”
Section: A Effect Of Cassava Accessions and Fertilizer Types On Disea...contrasting
confidence: 79%
“…It was shown that there was no significant effect of fertilizer on the disease severity of cassava plants. This is in disagreement with [33], who reported that NPK fertilizer application significantly increases CMD incidence and severity compared to trials without fertilizers. The disagreement observed in this investigation could have been as a result of high resistance of the improved cassava varieties used in this experiment to disease and pests.…”
Section: A Effect Of Cassava Accessions and Fertilizer Types On Disea...contrasting
confidence: 79%
“…Taken into consideration that the severity of local cultivars and an improved cultivar (8034) had severity of CMD higher in the leaves than in the cultivars TMS92/0326 and TMS961414. It is therefore evident that, a decrease in the cassava leave surface area followed by a decrease in the photosynthetic activities will result in a decrease in the crop to produce tubers; it has been demonstrated by Nkongolo [23] in his PhD thesis that CMD causes mosaic and leaf distortion, leading to defoliation and severe plant stunting.…”
Section: Severity Of Cmdmentioning
confidence: 99%